165k views
4 votes
25 POINTS!!!!!
Find the product. Show all your work.
(2y – 1)(4y – 3)

User Icecub
by
7.5k points

2 Answers

7 votes

Answer:

8y² - 10y + 3

Explanation:

In order to do this, you must use FOIL: First Outer Inner Last.

First, you must multiply the first terms in each parentheses:

2y(4y)=8y²

Next, you must multiply the two outer end numbers, which are 2y and -3:

2y(-3) = -6y

Then, you must multiply the two inner numbers, which are -1 and 4y:

-1(4y) = -4y

Finally, you must multiply the last numbers in each parentheses, which are -1 and -3:

(-1)(-3) = 3

Then, you add them all up:

8y²+(-6y)+(-4y)+3 = 8y² - 10y + 3

User Flornquake
by
7.9k points
1 vote

Answer:

8y^2 - 10y + 3

Explanation:

(2y – 1)(4y – 3)

Using FOIL

=(2y)(4y) -(2y)(3) - (1)(4y) - (1)(-3)

= 8y^2 - 6y - 4y + 3

= 8y^2 - 10y + 3

User UberMouse
by
9.4k points

No related questions found